Chinese ink: a programmable, dual-responsive and self-sensing actuator using a healing–assembling method. Issue 47 (30th November 2021) - Lin, Jian; Zhou, Peidi; Wen, Zhiyuan; Zhang, Wei; Luo, Zhiling; Chen, Luzhuo
Abstract : Chinese ink is introduced to fabricate multi-functional actuators with features of dual-responsiveness, programmable shape-morphing, healing and self-sensing function. Abstract : Actuators have wide applications in soft robotics and bionic devices. Since the healing ability not only makes actuators have longer service lives, but also allows them to be programmable through welding and assembling, it is regarded as an important feature for state-of-the-art actuators. Nevertheless, it remains a great challenge to integrate multi-functional merits, such as multi-responsiveness, programmable shape-morphing, healing and self-sensing function, simultaneously into a monolithic actuating material. Here, we introduce Chinese ink, a carbon-based material used in traditional calligraphy, to develop programmable, dual-responsive and self-sensing actuators by a healing–assembling method. The ink is combined with graphene oxide (GO) to fabricate a double-layer ink/GO actuator, which shows bi-directional bending under near-infrared light or humidity, owing to the mismatch of the volume change between ink and GO films. The maximal bending curvature is up to 5.2 cm −1 . Importantly, the entire ink/GO actuator can be healed with the aid of ink solution. Using the healing–assembling method to fabricate advanced structures including a Mobius ring, triangular rings and square rings, diverse actuating modes and complex 3D deformations such as a wavy shape and saddle shape are realized. This method also enables the construction of an artificial mimosa that shows a biomimetic stimulus-responsive behavior. In addition, the ink/GO actuator shows a self-sensing function, which is attributed to the thermoresistivity of the ink film. This research shows the huge potential of Chinese-ink-based actuators for use in smart materials, providing a new idea for the development of new generation multi-functional actuators.